(untitled) (Comillas Journal of International Relations, 2016)
Qatar played a leading role in supporting the opposition to Bashar al-Assad since the beginning of the Syrian uprising in 2011. While Kuwait emerged as a key (unofficial) conduit for financial transfers from the Gulf States to Syria and backing from Saudi Arabia initially took the form of illicit flows of militants and weapons to groups of opposition fighters, Qatar from the start adopted a political approach to organizing the Syrian opposition, in addition to providing tens of millions of dollars to rebel groups. Qatari support increasingly controversial as it was perceived to be tied to groups linked to the Syrian Muslim Brotherhood. During 2012, Qatar and Saudi Arabia backed competing groups, contributing to the fragmentation of the opposition, before responsibility for the “Syria file” passed decisively from Doha to Riyadh in spring 2013. This signified a major setback to Qatar’s ambition to become a regional power and highlighted how Qatar’s Syria policy was undermined by the lack of institutional capacity to underpin highlypersonalised decision-making processes.